2004
DOI: 10.5688/aj6805116
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing the Relevance of Chemistry to the Practice of Pharmacy Through theWho Wants to Be a Med Chem Millionaire?Learning Game

Abstract: The 2-semester medicinal chemistry course sequence required in the second-professional year of the pharmacy program at Creighton University, entitled, The Chemical Basis of Drug Action I and II, has always emphasized the importance of a thorough analysis of drug structure as an integral part of rational therapeutic decision-making. The instructors have routinely attempted to reinforce the professional relevance of drug chemistry by employing learning tools such as the medicinal chemistry case study (both paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 7 publications
4
32
0
1
Order By: Relevance
“…In the free-response portion of the survey tool, students acknowledged that the game was enjoyable, a result supported by classroom observations. This result is also in line with similar observations in previous studies, 3,4,9,14 indicating that increasing student enthusiasm for learning the subject matter is a primary strength of incorporating games into a curriculum.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the free-response portion of the survey tool, students acknowledged that the game was enjoyable, a result supported by classroom observations. This result is also in line with similar observations in previous studies, 3,4,9,14 indicating that increasing student enthusiasm for learning the subject matter is a primary strength of incorporating games into a curriculum.…”
Section: Discussionsupporting
confidence: 92%
“…Although the use of games in pharmacy education is widespread, [2][3][4][5][6][7][8][9] there are relatively few references in the literature to games that have been developed to enhance student learning of metabolic pathways. [10][11][12][13] Those that have been developed appear to be for general, undergraduate biochemistry courses and to emphasize the learning of intermediates and reactions, whereas features that may be more relevant to students in the health professions would include regulation of the pathways and their relationships to physiological events.…”
Section: Introductionmentioning
confidence: 99%
“…Description of games used in pharmacy education are found in several curriculum areas including the basic clinical sciences, patient care electives, and APPEs. [9][10][11][12][13][14][15][16] The literature supports that students enjoy playing educational games; however, there is some debate about how much educational games improve student learning. 10,15 To our knowledge, this study is the first to evaluate the use of a game-like tool for teaching medication history taking.…”
Section: Discussionmentioning
confidence: 99%
“…9 The majority of studies describing educational health care games found that students enjoyed playing them. [9][10][11][12][13][14][15][16] Games allow health care educators to create reallife scenarios without real-life consequences. The format of educational games creates a setting that decreases student stress and facilitates student learning.…”
Section: Introductionmentioning
confidence: 99%
“…6 Pharmacy faculty members are engaged in innovative pedagogical approaches to help their students form the connection between pharmaceutical sciences and pharmacy practice. Examples include redesigning courses to incorporate pharmacy-related examples, 7 intellectual games, 8 computerized cases studies, 9 and structurally-based therapeutic evaluation. 10 At the University of Cincinnati Winkle College of Pharmacy, faculty members identified the need for innovative and creative teaching methods to help struggling students gain an understanding of this critical connection.…”
Section: Introductionmentioning
confidence: 99%